Assessing the Impact of Chatbots on Customer Service Efficiency: A Comparative Study with Human Agents - Bilal, Fatima; Mezei, József; Alam, Badre (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This research investigates the way AI chatbots influence consumer service efficiency compared to human workers. The proliferation of chatbots across businesses emphasizes the importance of evaluating their impact on productivity, customer satisfaction, and service quality. Although chatbots are effective, they struggle with delicate or complicated interactions. Humans remain essential for providing sympathetic and thorough responses. This study reveals a significant gap in chatbots' ability to meet customer expectations, especially when individualized attention and trust are required. A quantitative research approach was used to collect survey data from customers having experience with both human agents and virtual assistants, i.e., chatbots. According to the findings, while routine inquiries are effectively handled by chatbots, they still struggle with contextual understanding and emotional intelligence. The ideal way to maximize client fulfillment and quality of service is to implement a service structure that combines chatbots for repetitive tasks and human agents for more complicated interactions. The study emphasizes how crucial it is to update chatbot systems frequently to satisfy evolving client demands and boost service effectiveness.